Respuesta :

6, The 3 is substituted into both functions and then added to each other. substituting 3 into f(x) gives 27, and substituting 3 into g(x) gives -21. Subtracting 21 from 27 gives 6. (27 + (-21) = (27 - 21) = 6

Answer: Hello!

here we got two functions, f(x) = 2x + 21, and g(x) = x -24, and we want to solve (f+g)(3).

the notation (f + g)(x) refers to the addition of both functions evaluated in the point x.

(f + g)(x) = f(x) + g(x) = (2x + 21) + (x - 24) = (2x + x) + (21 - 24) = 3x - 3

then, when x = 3 we have (f + g)(x) = 3*3 - 3 = 9 - 3 = 6

so the correct answer is the third one.

is the same as replacing x by 3 in both functions, and after that do the sum between them.

ACCESS MORE